Navigating Class, Religion, and Education: Exploring Nigerian Christian Middle-Class Dynamics in Nigeria - Berebon, Charles (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
The Nigerian middle class has been the subject of extensive sociological inquiry, yet the intersection of religion, education, and social mobility within this group remains underexplored, particularly among Christian communities in Lagos State. This paper examines the historical and contemporary factors shaping the emergence and reproduction of the Nigerian Christian middle class. Drawing on existing studies, the analysis highlights the role of missionary education, familial strategies, and professional advancement in fostering upward mobility. The heterogeneity of Christian denominations, stratification within religious communities, and the role of gender and migration are explored to provide a nuanced understanding of how Nigerian Christians navigate social hierarchies. The study also identifies gaps in current research, emphasizing the need for focused empirical studies to unpack the complex interplay of religion, class, and education. Findings contribute to the broader discourse on the sociology of religion and middle-class identity formation in Nigeria.